2019
DOI: 10.3390/ijms20133130
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain: Structural and Functional Changes in Brain Structures and Associated Negative Affective States

Abstract: Chronic pain is a condition in which pain progresses from an acute to chronic state and persists beyond the healing process. Chronic pain impairs function and decreases patients’ quality of life. In recent years, efforts have been made to deepen our understanding of chronic pain and to develop better treatments to alleviate chronic pain. In this review, we summarize the results of previous studies, focusing on the mechanisms underlying chronic pain development and the identification of neural areas related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
199
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 244 publications
(216 citation statements)
references
References 132 publications
(197 reference statements)
9
199
0
8
Order By: Relevance
“…The VAS score decreased from 7 to 5.6 at 2 weeks and then to 3.9 at 8 weeks after rTMS treatment. Other observational studies that predominantly involved patients with CPSP (35, 37-39) also showed the analgesic effect of high-frequency rTMS stimulation (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Central Pain After Strokementioning
confidence: 84%
See 1 more Smart Citation
“…The VAS score decreased from 7 to 5.6 at 2 weeks and then to 3.9 at 8 weeks after rTMS treatment. Other observational studies that predominantly involved patients with CPSP (35, 37-39) also showed the analgesic effect of high-frequency rTMS stimulation (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Central Pain After Strokementioning
confidence: 84%
“…Patients with painful conditions have various clinical outcomes. Acute pain conditions resolve over time after the normal healing process, but in some cases, they progress to chronic pain conditions that impact patients' quality of life (QoL) (5). Moreover, some patients with chronic pain do not respond to various conventional treatments, including drugs, injections with anesthetics and corticosteroids, and behavioral therapies (6).…”
Section: Introductionmentioning
confidence: 99%
“…Joint inflammatory pain is a highly prevalent condition [1,2], and the available treatments are often inefficient and have various adverse side-effects [3]. The pathophysiological mechanisms underlying pain, in these chronic conditions, are still not completely understood [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…">IntroductionJoint inflammatory pain is a highly prevalent condition [1,2], and the available treatments are often inefficient and have various adverse side-effects [3]. The pathophysiological mechanisms underlying pain, in these chronic conditions, are still not completely understood [4][5][6][7][8].Chronic pain involves many different complex processes in key spinal and supraspinal areas, which may suffer significant changes in an attempt to adapt to the ongoing noxious stimuli [4,5,7]. Indeed, the control of pain implies several molecular changes at the spinal cord, in the descending modulation of pain, and in supraspinal areas involved in the emotional component of pain processing [4,5,7,[9][10][11].…”
mentioning
confidence: 99%
“…Such chronic pain can cause neural plasticity or sensitization of the nervous system in the peripheral nerve, spinal cord, and brain. In other words, it induces alterations to the nervous system [ 3 ]. Thus, chronic pain should be considered not as a mere symptom of disease, but as a disease in itself of the nervous system.…”
Section: Introductionmentioning
confidence: 99%